Hoehnea grandiflora (Lamiaceae), a rare, critically endangered new species from southern Brazil - Funez, Luís Adriano; Hassemer, Gustavo (Phytotaxa, 2018)
We describe here Hoehnea grandiflora, a rare, critically endangered new species of Lamiaceae from high-elevation bogs in southern Brazil. The new species is similar to H. scutellarioides and can be distinguished by its shape and size of leaves, as some floral features. Its conservation status is assessed as Critically Endangered, because the new species is known from only one population located in an environmentally unprotected area. Urgent conservation studies and actions are necessary to prevent the extinction of this species. We also provide an identification key to the five species in the genus Hoehnea.